Homeplace : the Making of the Canadian Dwelling over Three Centuries. - Ennals, Peter (Heritage., 1998)
The authors present a new framework for interpreting the dwelling in Canada, including an important glimpse of counter-currents such as housing for gang labour, company housing, and the multi-occupant forms associated with urbanization.